FERMENTED PLANT BASED PRODUCTS IN EVERYDAY NUTRITION IN MACEDONIA AND THEIR POTENTIAL OF PROBIOTIC VECTORS - Levkov Vesna; Atanasova-Panchevska Natalija; Belichovska Daniela; Mojsova Sandra; Gjorgovska Natasha (Institute of Animal Science, R. N. Macedonia, 2022)
A b s t r a c t: Fermentation is one of the oldest processing techniques to extend the shelf life of perishable food and was particularly important before refrigeration. Although people can’t explain the processes, mechanisms and ini-tiators of fermentation, its peculiarity, the pleasant taste, durability of products and the positive influence over physio-logical and health condition of organism, encourages them to continue processing and consuming this kind of food. Fermented vegetables, peppers with cottage cheese (piperki so urda), sauerkraut (fermented cabbage), pickled cucum-bers, boza (cereal fermented beverage), and apple vinegar produced in households in different regions in Macedonia can be rich source of different species lactic acid bacteria and yeasts. The aim of this study was to indicate Macedonian fermented plant products and beverages as food with positive influence over physiological and health condition and as vectors of potential probiotics.
Keywords: fermented vegetables; fermented cereal beverage; health benefits; probiotic vectors